STRATEGI KEPEMIMPINAN KEPALA SEKOLAH MEMPERSIAPKAN PERSONEL LEMBAGA PENDIDIKAN MENGHADAPI TANTANGAN PERUBAHAN - Puspita, Nimas Bella; Triwiyanto, Teguh (STKIP Pesisir Selatan, 2022)
This study aims to determine the principal's leadership strategy to prepare educational institution personnel in facing the challenges of change in the global era. The method used in this research is literature study. Based on the review of the journal, it can be concluded that there are two leadership styles that can be applied by school principals to face the challenges of change in the global era, namely change leadership and situational leadership. Change leadership is an attempt to shape fundamental changes in the organization with the aim of creating more useful organizational values. While situational leadership is a leadership style that emphasizes flexibility and skills in combining leadership styles based on the situation faced by the principal.